2021
DOI: 10.1002/aenm.202101343
|View full text |Cite
|
Sign up to set email alerts
|

Water‐Soluble Salt Template‐Assisted Anchor of Hollow FeS2 Nanoparticle Inside 3D Carbon Skeleton to Achieve Fast Potassium‐Ion Storage

Abstract: The rationally structural engineering is an efficient strategy to improve the comprehensive performance of potassium‐ion storage anode materials. In this paper, a hybrid with hollow FeS2 nanoparticles anchored into the 3D carbon skeleton (labeled as H‐FeS2@3DCS) is successfully constructed through two critical steps of in situ chemical deposition and anion‐exchange reaction strategies. In the former, the water‐soluble Na2CO3 crystals are used as hard templates for the preparation of 3DCS, while Fe3+‐containing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(35 citation statements)
references
References 77 publications
2
28
0
Order By: Relevance
“…5c shows peaks corresponding to K–S bonds, S-doping in carbon, and oxidized sulfur species (SO x ). 43–45 SO x species may have formed because of electrolyte decomposition, which has also been observed in other ex situ studies. 50 The K 2p spectrum shown in Fig.…”
Section: Resultssupporting
confidence: 76%
See 2 more Smart Citations
“…5c shows peaks corresponding to K–S bonds, S-doping in carbon, and oxidized sulfur species (SO x ). 43–45 SO x species may have formed because of electrolyte decomposition, which has also been observed in other ex situ studies. 50 The K 2p spectrum shown in Fig.…”
Section: Resultssupporting
confidence: 76%
“…5d) revealed several peaks corresponding to the Fe–S and K–S bonds in the K x FeS 2 material, S-doping in carbon, and SO x -related materials. 43–45 The normalized intensity of the K 2p spectrum for the charged state, shown in Fig. 5f, was much smaller than that of the discharged state, which may be due to the decomposition of some SEI layers.…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…5–9 Compared with SIBs, PIBs are more likely to possess high energy density because the redox potential of K/K + (−2.93 V) is lower than that of Na/Na + (−2.71 V) and close to that of Li/Li + (−3.04 V), and seem to be the most promising alternative to LIBs in the large-scale energy storage field. 10–14 Notably, extensive research has been reported to explore high-performance anode materials, such as carbonaceous materials, 15–18 MXenes, 19 transition metal sulfides, 20–23 and alloys. 24–28 Compared with the widely available anode materials, only a limited amount of cathode materials have been reported for PIBs because of rigorous intercalation conditions arising from the larger size of K + .…”
Section: Introductionmentioning
confidence: 99%
“…Hence, the pseudocapacitive effect (k 1 v) and ions diffusion insertion process (k 2 v 1/2 ) can be calculated by ascertaining the constants of k 1 and k 2 based on the simplified equation of i/v 1/2 = k 1 v 1/2 + k 2 . [36,37] As displayed in Figure 5c, the total capacity is dominant by the ion diffusion effect with the ratio of 20.8 % at 0.2 mV s À 1 . With an increase in the sweep rates, the percentage of capacitive-controlled behavior gradually increased and finally reached 97.1 % at 1.0 mV s À 1 .…”
Section: Chemelectrochemmentioning
confidence: 91%